Product proliferation strategies and firm performance: The moderating role of product space complexity - Barroso, Alicia; Giarratana, Marco S. (Strategic Management Journal, 2013)
In the Spanish automobile market between 1990 and 2000, significant reductions in tariff and nontariff protections increased the complexity of the product space, through the penetration of new car brands and models. Acknowledging these environmental dynamics, this study details conditions in which across‐niche (product breadth or intraindustry diversification) and within‐niche (product depth or versioning) product proliferation exerts a positive relationship on firm performance, as well as how key relationships change according to the complexity of the product space in the industry . Copyright © 2013 John Wiley & Sons, Ltd.